Presumptive design design provocations for innovation - Frishberg, Leo; Lambdin, Charles (Morgan Kaufmann, imprint of Elsevier, 2016)
"Presumptive design: design provocations for innovation is for people "inventing" the future: future products, services, companies, strategies, and policies. It introduces a design-research method that shortens time to insights from months to days. Presumptive design is a fundamentally agile approach to identifying your audiences' key needs. Offering rapidly crafted artifacts, your teams collaborate with your customers to identify preferred and profitable elements of your desired outcome. Presumptive design focuses on your users' problem space, informing your business strategy, your project's early-stage definition, and your innovation pipeline. Comprising discussions of design theory with case studies and how-to's, the book offers business leadership, management and innovators the benefits of design thinking and user experience in the context of early-stage problem definition. Presumptive design is an advanced technique and quick to use." -- Provided by publisher